2023
DOI: 10.31098/jefltr.v3i1.1414
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Personality Traits, Class Level, and Gender on EFL Learners' Online Learning Acceptance among Tunisian University Students

Abstract: The outbreak of the COVID-19 pandemic necessitated the transition from in-person instruction to online education. Most students in Tunisia repudiated such sudden transfer. This study, then, probes into factors that impact the online learning experience during the pandemic. Hence, it investigates the effect of affective variables, namely personality traits, on learners' acceptance of online learning in the Tunisian EFL formal university context. Additionally, it scrutinizes the relationship between remote learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…All informants were female, and they were not asked about their sexual preferences. This information is needed because the results may be different if the user is a man or woman with certain sexual preferences, because certain expressions can be influenced by gender and personality (Bouzayenne, 2023;Liannita et al, 2023;Budiarti, 2022).Researchers found that on average, they started using lipstick since high school. One informant had used lipstick at the junior high school level, and the other had used it since entering university.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…All informants were female, and they were not asked about their sexual preferences. This information is needed because the results may be different if the user is a man or woman with certain sexual preferences, because certain expressions can be influenced by gender and personality (Bouzayenne, 2023;Liannita et al, 2023;Budiarti, 2022).Researchers found that on average, they started using lipstick since high school. One informant had used lipstick at the junior high school level, and the other had used it since entering university.…”
Section: Findings and Discussionmentioning
confidence: 99%